(untitled) (CIPEEX, 2022)
TATTOOING IS AN ACT OF BODY EXPRESSION AND SOCIAL COMMUNICATION WITH GREAT POPULARITY BECAUSE IT WORKS AS AN INDIVIDUAL SUBJECTIVATION. FOR BEING AN INVASIVE PROCEDURE, WHICH BREAKS THE EPITHELIAL BARRIER, IT ACTS AS A POTENTIAL SOURCE OF INFECTION AND CONTAMINATION. THE INK IS ONE OF THE PROTAGONISTS FOR THIS TO OCCUR.